Atopic dermatitis and association of risk for primary immune thrombocytopenia and autoimmune diseases among children: A nationwide population-based cohort study. Issue 29 (July 2016) - Wei, Chang-Ching; Lin, Cheng-Li; Shen, Te-Chun; Tsai, Jeng-Dau
Abstract : Abstract: Primary immune thrombocytopenia (ITP) is currently defined as an acquired autoimmune disorder with persistent thrombocytopenia. However, the temporal interaction between T helper type 2 cell (Th2)-mediated allergic diseases and T helper type 1 cell (Th1)-mediated ITP remains unknown. Atopic dermatitis (AD) is considered one of the first steps in the atopic march. Herein, we conducted a population-based cohort analysis to investigate the risk of ITP in children with AD in comparison with non-AD controls. We subsequently compared the occurrence of other autoimmune diseases in ITP children in both AD and non-AD cohorts. From 2000 to 2007, 120, 704 children with newly diagnosed AD and 241, 408 randomly selected non-AD controls were included in the study. By the end of 2008, incidences of ITP in both cohorts and the AD cohort to non-AD cohort hazard ratios (HRs) and confidence intervals (CIs) were measured. Comparison of the occurrence of other autoimmune diseases in ITP between children with and without AD was analyzed. The incidence of ITP during the study period was 1.72-fold greater (95% CI: 1.13–2.62) in the AD cohort than in the non-AD cohort (6.96 vs 4.00 per 100, 000 person-years). The risk was greatest among male children, children >2 years, those in densely populated areas, and those with white-collar parents. The HR of ITP in AD children increased significantly with the number of AD-related clinical visits ( P < 0.001). The risk of developing ITP in the AD cohort was highest within the first 3 years after the diagnosis of AD (HR: 1.78; CI: 1.14–2.78). The AD cohort with ITP had a higher occurrence rate of other autoimmune diseases than the non-AD cohort with ITP. AD children had a greater risk of developing ITP and other autoimmune diseases. Further research is needed to clarify the role of allergy in the pathogenesis of ITP and autoimmune diseases.